More than an antidote against amnesia…: Some historiographical, theoretical and methodological reflections on the History of Education - Depaepe, Marc (Neveléstudomány | Oktatás – Kutatás – Innováció, 2013)
This article observes the paradigm shift in the history of education through different time periods. The author departs from his perspective as a historian and educator, while comparing authors who have dealt with the same thematic discourse. The realisation of the challenges of the so-called ‘new cultural history of education’ by a new academic approach invites to experience the so necessary historical contextualisation.